A Novel RP- UPLC Technique for the Simultaneous Estimations of Olanzapine and Samidorphan in Bulk and Tablet Dosage Form (International Journal of Food and Nutritional Sciences, 2023)
A convenient, precise, consistent, and robust quantitative approach was established for separationand simultaneous quantification of olanzapine and samidorphan in combination. The isocraticelution was attained by Hibar C18 (100 × 2.1mm, particle size 2µ) column at a flow rate of0.3ml/min and temperature was maintained at 30°C.